Effects of Fungicide Propiconazole on the Yeast-Like Symbiotes in Brown Planthopper (BPH, Nilaparvata lugens Stål) and Its Role in Controlling BPH Infestation - Shentu, Xuping; Wang, Xiaolong; Xiao, Yin; Yu, Xiaoping (Frontiers in Physiology, 2019)
Yeast-like symbiotes (YLS), harbored in the abdomen fat-body cells of the rice brown planthopper (BPH), Nilaparvata lugens Stål (Hemiptera: Delphacidae), are vital to the growth and reproduction of their host. It is feasible to manipulate BPH infestation on rice by inhibiting YLS using fungicide. In this study, the fungicide propiconazole was injected into the hemolymph of BPH thorax via microinjection to investigate its effect on YLS, especially the dominant species, Hypomyces chrysospermus, and their host BPH. Propiconazole markedly reduced the total number of YLS and H. chrysospermus in BPH hemolymph and fat body, thereby leading to an obvious higher mortality and lower fecundity of BPH than the negative control (PBS, phosphate buffer solution). After microinjecting propiconazole, the survival rate of BPH nymphs at the 5th instar was significantly lower than that obtained after PBS treatment. Eight days after propiconazole microinjection, the BPH survival rate dropped to 40%, only half of BPH survival rate treated with PBS microinjection. For female adults (1 day old), there were significant differences in the survival rates between BPHs treated with propiconazole and those treated with PBS at days 5–8. The fecundity of BPH decreased significantly by microinjecting propiconazole and averaged only 229 eggs per female, which was 20% less than that of the negative control. Furthermore, we reared BPH on the susceptible variety TN1 sprayed with propiconazole to prove the feasibility manipulating field occurrence of BPH by inhibiting YLS using fungicides. The number of YLS and H. chrysospermus in BPH obviously declined. Subsequently, the survival rate and fecundity of BPH significantly decreased after feeding on rice treated with propiconazole. Meanwhile, the propiconazole residue was detected in the hemolymph and gut of BPH by HPLC analysis within 1 d of feeding. Inhibiting YLS using fungicides was a novel and effective way to control BPH infestation.